Identifiying factors that influence consumer adoption towards usage of online service (e-Caruman) at EPF Kuantan / Wan Nurhafizah Mohd Rodzlad - Mohd Rodzlad, Wan Nurhafizah (Bachelor of Science (Hons.) Statistics, 2015)
The main focus for this study was to determine the relationship between usage of online service (e-caruman) and consumer adoption. Besides that, these studies also aim to examine the factor influence consumer adoption towards using of online service (e-caruman). Other than that, to study the significance difference mean between levels of education among consumer adoption on using online service also one of the objective in this study. There are four variable include in this study which are competence, convenience, and security variable as independent variable. While the consumer adoption as a dependent variable. This study involved 150 respondents by using simple random sampling (SRS) and the data was collected by using questionnaire method. The methods of data analysis used were Pearson correlation, Multiple Linear Regression and One Way ANOVA. The finding showed that all independent variable have a strong positive linear relationship with response variable and there is significant factor influence consumer adoption towards usage of online service (e-caruman) which are convenience and security towards consumer adoption. Meanwhile, the one way ANOVA test shows that there is significance difference between levels of education among consumer adoption